Mapping the development of disabled people's organizations in China: main types and current status. Issue 2 (7th February 2022) - Wu, Xinye; Wu, Weixu
Abstract: Little is known about China's disabled people's organizations (DPOs) in the current research literature. This article, partly in response to the prior journal article by Zhang (Disability & Society 32 (7): 1096–1101, 2017), attempts to map the four main types of DPOs in China and analyze their current status using the case of Shanghai. In addition to the Disabled Persons' Federation, the other types include five specialized associations, nonprofit organizations, and voluntary groups. This study preliminarily presents the number of DPOs, their government funding and changing registration management system. It is hoped that researchers will pay more attention to DPOs in non-Western settings and perform more comparative studies between China and other developed countries in the future.